Geomorphology, Sedimentary Structures, and Genesis of Dome Dunes in Western Canada - Halsey, Linda; Catto, Norman (Géographie physique et Quaternaire, 1994)
ABSTRACTDome dunes in four stabilized, inland dune fields in western Canada are predominantly composed of horizontal to low-angle cross-strata, indicating that slip face development was rare. Dip angles of lee side deposits decrease upward in the dome dunes. The spread of dip directions increases with elevation in the dunes, spanning 360° for topset deposits. Sedimentary structures indicative of moisture (adhesion laminae) and vegetation (scour surfaces) occur in the dunes and denivation features are also present. Sediment adhesion is responsible for the maintenance of the dome morphology. Sediment sorting within the dome dunes is poorer than in other local dune types in the vicinity, suggesting that less reworking/ineffective selective transport occurred and that the dome dunes are more efficient in retaining sediment. The rarity of slip face and grainfall deposits and the abundance of low angle deposits indicate that preferential accumulation of sediment at the top of the lee side did not occur. Development of domal morphology is a consequence of the inhibition of slip face development. In inland, relatively moist boreal environments, the primary factor limiting or precluding sediment accumulation at the crest of the dunes is a low rate of sedimentation.